ANALISIS FAKTOR PENYEBAB KERUSAKAN NASKAH KUNO KOLEKSI ABDUL MULKU ZAHARI DI KELURAHAN BAADIA KECAMATAN MURHUM KOTA BAUBAU PROVINSI SULAWESI TENGGARA - Mustika Mustika; Syahrun Syahrun; agus supriatna (SANGIA: Jurnal Penelitian Arkeologi, 2020)
This study aims to determine and explain the types of damage and the factors causing the damage and solutions to repair the ancient manuscripts collected by Abdul Mulku Zahari in Baadia Village, Murhum District, Baubau City.Research using qualitative research with inductive reasoning is drawing conclusions from things that are specific then states it into things that are general in nature, with data collection methods consisting of observation, literature studies, interviews and documentation. The results of research there are several types of damage and ancient manuscripts in the collection of Abdul Mulku Zahari in Baadia Village, Murhum District, Baubau City, namely: pen streaks, yellowing paper, black spots, ink seeping and widened, torn and faded writing. Factors causing damage to ancient manuscripts in the collection of Abdul Mulku Zahari In the Baadia Village, Murhaum District, Baubau City are divided into four factors causing damage, namely: damage caused by temperature and humidity including fungal factors caused by human damage that comes from the owner or colleagues. fellow of the owner of the manuscript itself, damage caused by insects including termites, rats, nerds and cockroaches, damage factor caused by nature, caused by water that causes ink to seep and widen so that the writing on the manuscript is not clearly read and makes the text corrupt . Efforts to prevent damage to the collection of Abdul Mulku Zahari manuscripts are to put anti-insect drugs such as mothballs and Slica Gel and regulate air temperatures and humidity that are ideal for ancient manuscripts, so that fungus does not multiply which can damage the ancient manuscripts. as well as digitizing scripts to maintain script files in order to stay awake in digital form.